Hydration behavior by X-ray diffraction profile fitting of smectite-bearing minerals in a Plio-Pleistocene mudrock from Eugene Island, Gulf of Mexico. (April 2019) - Day-Stirrat, Ruarri J.; Bryndzia, L. Taras; Schleicher, Anja M.; Adriaens, Rieko; Hofmann, Ronny; Flemings, Peter B.
Abstract: Clay mineral hydration and dehydration processes are reversible at temperatures <100 °C and strongly affect wellbore stability, fines migration, permeability, and dispersion of pore pressure. The hydration behavior of smectite-rich material as a function of relative humidity (activity of water, a w, controlled by salinity) and temperature was studied using in situ X-ray diffraction on a material retrieved from coring in the Gulf of Mexico. X-ray diffraction profile fitting was used to explore the competition for water between hydratable phases across a range of relative humidity, 2% to 90%, and temperature, 25 °C to 95 °C, conditions. X-ray diffraction profile fitting of Eugene Island material employed a modified multi-specimen approach in which proportions of minerals were modelled using Ca-exchanged preparations in air-dried and ethylene glycol solvated states. Across the range of hydration states, the mineral proportions and crystallographic parameters remained constant from the multi-specimen approach and only the number of water layers in hydratable phases varied. Quantitative clay mineralogy of Eugene Island (Gulf of Mexico), sourced material showed a natural material with a discrete smectite component and a mixed-layered illite-smectite, both capable of hydration/dehydration. A sample from the Jurassic Haynesville Formation was used as a control sample to reflect high thermal and diagenetic maturity with low CEC and expandability. This illite dominated sample had no hydration/dehydration behavior with changes in relative humidity and temperature. Results of this study predict that changes in pore water salinity, represented by variable RH or a w, could also be a viable mechanism for generating overpressures in smectite-rich sediments during early burial where the degree of overpressure is controlled by the total sedimentation rate, the ratio of permeability to compressibility, and time. Additionally, the discrete smectite component and the mixed-layered illite-smectite hydrated differently. Discrete smectite hydrates more water at lower relative humidity than the mixed-layered illite-smectite. Highlights: Differential hydration pathways for smectite bearing clays in the same sample. A modified multi-specimen approach for X-ray profile modeling in variably hydrated smectites. Secondary overpressure formation mechanism in low permeability mudrocks.